Characteristics of 24 SARS-CoV-2-Sequenced Reinfection Cases in a Tertiary Hospital in Spain - Blanca Borras-Bermejo; Maria Piñana; Maria Piñana; Cristina Andrés; Cristina Andrés; Ricardo Zules; Alejandra González-Sánchez; Alejandra González-Sánchez; Juliana Esperalba; Juliana Esperalba; Oleguer Parés-Badell; Damir García-Cehic; et al. (Frontiers in Microbiology, 2022)
BackgroundSince the emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the main concern is whether reinfections are possible, and which are the associated risk factors. This study aims to describe the clinical and molecular characteristics of 24 sequence-confirmed reinfection SARS-CoV-2 cases over 1 year in Barcelona (Catalonia, Spain).MethodsPatients with > 45 days between two positive PCR tests regardless of symptoms and negative tests between episodes were initially considered as suspected reinfection cases from November 2020 to May 2021. Whole-genome sequencing (WGS) was performed to confirm genetic differences between consensus sequences and for phylogenetic studies based on PANGOLIN nomenclature. Reinfections were confirmed by the number of mutations, change in lineage, or epidemiological criteria.ResultsFrom 39 reported suspected reinfection cases, complete viral genomes could be sequenced from both episodes of 24 patients, all were confirmed as true reinfections. With a median age of 44 years (interquartile range [IQR] 32–65), 66% were women and 58% were healthcare workers (HCWs). The median days between episodes were 122 (IQR 72–199), occurring one-third within 3 months. Reinfection episodes were frequently asymptomatic and less severe than primary infections. The absence of seroconversion was associated with symptomatic reinfections. Only one case was reinfected with a variant of concern (VOC).ConclusionSevere acute respiratory syndrome coronavirus 2 reinfections can occur in a shorter time than previously reported and are mainly found in immunocompetent patients. Surveillance through WGS is useful to identify viral mutations associated with immune evasion.